Marangoni effect of a gas bubble migration - Muhamad Naim Aman. (2011)
When a bubble is formed in a temperature field, the surface tension effect is significant on the moving of bubble. The phenomenon is important in the micro- or nano- scale manufacturing or in the space activities. The present project is to study the effect the transport driven by the temperature gradient which is called Marangoni effect. Five experiments were done in 3 different temperature fields, two in a uniform room temperature and the other three were done in a temperature gradient of ∆T 0.05 k/mm., ∆T 0.31k/mm and ∆T 1.33k/mm. The experiment is done in two test cell, one in a cell of dimension of 40 x 40 x 60 mm and the other is of dimension 10 x10 x 20 mm. A high speed camera is use to capture the bubble migration with a help of a camera light. The results show that the bubble in the room temperature has an almost constant velocity when it reached to top of the test cell and finish longer compare with the experiment done in the temperature gradient. When compare with the bubble that was formed in the temperature field, it was shown that the velocity of the bubble in the temperature gradient is higher due to Marangoni effects. This paper have proven by inducing a temperature gradient, it create a Marangoni effect which pulled the bubble towards the hotter region. For future experiment, should deal with two or more bubbles and their interaction. The parameter range of Re and Ma should be extended to understand the non linear effects. This experiment is important in the field of nano and micro scale manufacturing or crystal growing, as this micro or nano bubble may cause weakness in the material and crystal. Since the bubble is so small, we can depend on the buoyancy migration to remove the bubble and by applying temperature gradient it will help removed the bubble.